DEVELOPING PISA-LIKE MATHEMATICS TASK WITH INDONESIA NATURAL AND CULTURAL HERITAGE AS CONTEXT TO ASSESS STUDENTS MATHEMATICAL LITERACY - Oktiningrum, Wuli; Zulkardi, Zulkardi; Hartono, Yusuf (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2016)
The aim of this research is produce a set of PISA-like mathematics task with IndonesiaÃ‚Â natural and cultural heritage as context which are valid, practical, to assess studentsÃ¢â‚¬â„¢Ã‚Â mathematics literacy. This is design research using type of development research withÃ‚Â formative evaluation. A total of 20 students of SMP Negeri 1 Palembang. Beside, 10 expertsÃ‚Â were involved in this research to assess the feasibility of prototyping in terms of content,Ã‚Â context and language. Walk through, documentation, questionnaire, test result, and interviewsÃ‚Â are way to collect the data. This research produced a PISA-like math task is as many 12Ã‚Â category of content, context, and process valid, practical and has potential effect. The validityÃ‚Â came empirical evaluation of validation and reliability testing during small group. From theÃ‚Â field test, we conclude that the tasks also potentially effect to the studentsÃ¢â‚¬â„¢ mathematicalÃ‚Â literacy in activating the indicators of each Fundamental Mathematical Capabilities.Keywords: development research, PISA task, mathematics literacy, fundamental mathematical capabilitiesÃ‚Â DOI: http://dx.doi.org/10.22342/jme.7.1.2812.1-8